Aberrant intestinal stem cell lineage dynamics in Peutz–Jeghers syndrome and familial adenomatous polyposis consistent with protracted clonal evolution in the crypt. Issue 6 (22nd September 2011) - Langeveld, Danielle; Jansen, Marnix; de Boer, D V; van Sprundel, Mariska; Brosens, Lodewijk A A; Morsink, Folkert H; Giardiello, Francis M; Offerhaus, G Johan A; de Leng, Wendy W J
Abstract : Objective: Genetic predisposition to cancer in Peutz–Jeghers syndrome (PJS) and the role of germline serine–threonine kinase ( LKB1 ) mutations are poorly understood. The authors studied the effect of germline LKB1 mutations on intestinal stem cell dynamics in unaffected flat PJS mucosa. Recent research has documented that the intestinal crypt houses multiple equipotent stem cell lineages. Lineages continuously compete through random drifts, while somatically inherited methylation patterns record clonal diversity. Design: To study the effect of germline LKB1 mutations on clonal expansion, the authors performed quantitative analyses of c ardiac- s pecific homeobo x methylation pattern diversity in crypts isolated from unaffected colonic mucosa obtained from archival PJS patient material. The authors compared methylation density and methylation pattern diversity in patients with PJS to those in patients with familial adenomatous polyposis and age-matched controls. Results: The percentage of total methylation is comparable between groups, but the number of unique methylation patterns is significantly increased for patients with familial adenomatous polyposis and patients with PJS compared to control subjects. Conclusions: Monoallelic LKB1 loss is not silent and provokes a protracted clonal evolution in the crypt. The increased methylation pattern diversity observed in unaffected PJS mucosa predicts that premalignant lesions will arise at an accelerated pace compared to the general population.